Adsorption technology in water treatment : fundamentals, processes, and modeling - Worch, Eckhard, 1951- (De Gruyter, 2012)
This scientific monograph treats the theoretical fundamentals of adsorption technology for water treatment from a practical perspective. It presents all the basics needed for experimental adsorption studies as well as for process modeling and adsorber design. With the increasing importance of micropollutants in the water cycle, particular attention is paid to their competitive adsorption in presence of background organic matter. Clear illustrations, extensive literature references make this work indispensible for scientists and technicians involved in water treatment.